Implementasi Perancangan Tata Kelola Teknologi Informasi menggunakan Kerangka Kerja COBIT 4.1 pada Bidang Pengelolaan Teknologi Informasi dan Komunikasi (TIK) Diskominfo Kota Madiun - Debrilla Ivanadya Pang; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The management of ICT field of The Communication and Information office of Madiun is a government agency that has responsibility in managing of ICT to supporting technology information service so that it requires an evaluation of managing ICT. This research employs a COBIT 4.1 framework, which is focused on the domain Deliver and Support (DS) especially on DS1 the definition and management service level, DS5 ensure systems security, DS7 training and education of the user, DS11 manage data. The purpose of this research is to know the evidence of governance ICT, the result of maturity level and provide results recommendation to documentation design on governance such as policy, standards, guidelines and procedures. Based on this research, the average value of maturity level that is obtained from each subdomain DS1, DS5, DS7, and DS11 it is 2.83, 2.59, 2.75 and 2.58 and analytic value gap is 1,00. To achieve the maturity level of expectations 3.00 then the recommendation given is to make policy, to make standard procedure and to do documentation using standard format so that the management of ICT field can manage the ICT with a clear and controlled stage.